2021
DOI: 10.4081/ija.2021.1800
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic nitrogen coupled with seaweed extract and microbial inoculants improves rice (<em>Oryza sativa</em> L.) production under a dual cropping system

Abstract: The over-reliance on synthetic nitrogen (N) in current farming is a major concern because of its adverse effects on soil quality, the environment, and crop production. Organic fertilizers such as seaweed extract (SE) and microbial inoculants (MI) provide alternatives to chemical fertilizers that could decrease the amount of synthetic N needing to be applied and improve crop growth productivity. This study evaluated the combined effect of SE and MI with reduced N rates on the growth, biomass accumulation, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…These cultivars require less N and P for their growth and development (Li et al, 2019). Our results are consistent with those of Ali et al (2020), showing that proper N application can increase the number of tillers and LAI of rice and promote its growth but that the excessive application of N fertilizer increases the number of ineffective tillers and reduces the utilization of N (Xie et al, 2021). However, several studies have reported that reducing N and P fertilizer application reduces rice growth traits (Jiang et al, 2021;Murthy et al, 2015) and alters rice flowering days (Ye et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These cultivars require less N and P for their growth and development (Li et al, 2019). Our results are consistent with those of Ali et al (2020), showing that proper N application can increase the number of tillers and LAI of rice and promote its growth but that the excessive application of N fertilizer increases the number of ineffective tillers and reduces the utilization of N (Xie et al, 2021). However, several studies have reported that reducing N and P fertilizer application reduces rice growth traits (Jiang et al, 2021;Murthy et al, 2015) and alters rice flowering days (Ye et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Our previous study at the same experimental sites was conducted with the same cultivars, which show no significant effect among experimental sites for rice yield. However, their results were significant among the treatments across the experimental sites (Xie et al, 2021).…”
Section: Experimental Sites and Weathermentioning
confidence: 80%
See 1 more Smart Citation
“…Excessive synthetic N fertilization causes significant environmental problems, such as increased greenhouse gas emissions and groundwater contamination, particularly leading to degradation of soil physicochemical and biological properties (Y. Luo et al., 2020; Sarma et al., 2017; Y. Zhang et al., 2019). Moreover, the continued application of chemical fertilizers (CFs) has also increased the soil acidification and compaction of arable soils, thereby suppressing plant growth and production (Iqbal et al., 2019; Ullah et al., 2021; H. Xie et al., 2021). Therefore, this continued reliance on CFs for cereal crop production is not sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic matter is key for improving crop production because of the role it plays in sustaining and improving soil physical, chemical, and biological properties (Iqbal et al., 2019; Sarker et al., 2018). In the current farming system, over‐reliance on chemical fertilizers is the main reason for the decline in soil health and stagnant rice yields, as chemical fertilizers have negative effects on soil properties, the environment, and crop productivity (Ali, He, et al., 2020; Cai et al., 2018; Iqbal et al., 2020; H. Xie et al., 2021). Ecological concerns over the deterioration in soil health, rice production, and environmental quality in the present farming system could be addressed by encouraging the in‐situ recycling of crop residues and altered tillage practices (Blumfield & Xu, 2003; Saikia et al., 2019; Jing Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%